2018
DOI: 10.1063/1.5036951
|View full text |Cite
|
Sign up to set email alerts
|

Experimental validation of the hybrid scattering model of installed jet noise

Abstract: Jet installation causes jet noise to be amplified significantly at low frequencies and its physical mechanism must be understood to develop effective aircraft noise reduction strategies. A hybrid semi-empirical prediction model has recently been developed based on the instability-wave-scattering mechanism. However, its validity and accuracy remain to be tested. To do so, in this paper we carry out a systematic installed jet-noise experiment in the laboratory using a flat plate instead of an aircraft wing. We s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Suffice to mention here that although the Reynolds number in Tanna's study is twice as large as that used in our study, the agreement between the two is good enough to show that the measurement is reliable. Details of this validation can be found in Lyu and Dowling (2018a). In what follows, we will start by showing the results for isolated jet noise.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Suffice to mention here that although the Reynolds number in Tanna's study is twice as large as that used in our study, the agreement between the two is good enough to show that the measurement is reliable. Details of this validation can be found in Lyu and Dowling (2018a). In what follows, we will start by showing the results for isolated jet noise.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that the low-frequency noise intensification observed in installed jets is due to the scattering of jet instability waves (Lyu and Dowling 2016, 2018aCavalieri et al 2014). The understanding of this mechanism is important in developing new noise reduction methods.…”
Section: Introductionmentioning
confidence: 99%
“…Using (2.24), both the spectra and the directivity patterns of the far-field sound can be readily plotted. Since the model needs an input of the near-field pressure spectra, in this paper we use the spectra measured in the experiment carried out by the authors in an earlier study , 2018. This experiment was carried out in the anechoic chamber at the Engineering Department at the University of Cambridge, where a round, cold, Mach 0.5 jet of diameter 2.54 cm was operated both with and without a nearby flat plate.…”
Section: Resultsmentioning
confidence: 99%
“…This experiment was carried out in the anechoic chamber at the Engineering Department at the University of Cambridge, where a round, cold, Mach 0.5 jet of diameter 2.54 cm was operated both with and without a nearby flat plate. For a detailed description of the experimental setup used to measure the near-field pressure spectra, the readers are referred to the earlier works , 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In this section, the near-field hydrodynamic pressure -edge scattering model developed by Lyu and Dowling [1] for the modelling of the jet-installation noise is presented. The source parameters herein will be obtained from the LES simulation.…”
Section: Acoustic Noise Modelsmentioning
confidence: 99%